The temperature distribution eximer laser source (193 nm) within a human eye and review on some side-effects - Shahi, Sharifeh; Khorvash, M.; Harun, Sulaiman Wadi; Ahmad, Harith; Golnabi, Hossein (American-Eurasian Network for Scientific Information, Jordan, 2010)
A mathematical model to predict the temperature distribution within the human eye when subjected to a laser source (193nm) is presented. In this paper the thermal effects of the laser radiation on different parameters of the eye and some side-effects are discussed. The influence of parameters such as the heat conductivity, diffusivity, the scattering and refraction coefficients are compared and the damage threshold conditions for temperature distribution are estimated. Other factors such as the color of eye, the ageing factor of the human eye and anxiety are also studied in this report. The interaction of the laser sources within the eye medium is described by employing the Penne's bioheat transfer equation. Uncertainties for predicted temperatures of the eye tissues due to approximate parameters are used based on analyzing one-dimensional heat transfer subject to the boundary conditions.